Macroinvertebrate responses to nickel in multisystem exposures. (January 2016) - Custer, Kevin W.; Kochersberger, Jon P.; Anderson, Padrick D.; Fetters, Kyle J.; Hummel, Steven; Burton, G. Allen
Abstract: Metals introduced to sediments undergo a variety of complexation and partitioning changes that affect metal bioavailability. Using simultaneously extracted metal (SEM)/acid volatile sulfide (AVS) and organic carbon ( f OC ) models, the authors examined nickel (Ni) toxicity and bioavailability in 2 field studies (using streamside mesocosm and in situ colonization) and 1 laboratory study. The streamside mesocosm experiments indicated that benthic communities (Ephemeroptera, abundance, and taxa richness) responded negatively to increasing SEMNi /AVS and (SEMNi –AVS)/ f OC models. In the in situ colonization study, taxa richness, abundance, and Ephemeroptera, Plecoptera, and Trichoptera (EPT) taxa decreased with increasing SEMNi and SEMNi /AVS values. Nickel‐spiked sediments were tested in the laboratory with indigenous field‐collected mayflies ( Anthopotamus verticis, Isonychia spp., and Stenonema spp) and a beetle ( Psephenus herricki), and with laboratory‐cultured Hyalella azteca and Chironomus dilutus . The amphipod H. azteca was the most sensitive organism tested, and the mayflies Anthopotamus verticis and Stenonema spp. were the most sensitive indigenous organisms to Ni‐spiked sediments. These studies help discern which factors are important in determining Ni toxicity and bioavailability at the individual, population, and community levels. Environ Toxicol Chem 2016;35:101–114. © 2015 SETAC